Comparative effects of vitamin C on the effects of local anesthetics ropivacaine, bupivacaine, and lidocaine on human chondrocytes - Tian,Jun (2016)
BACKGROUND: Intra-articular injections of local anesthetics are commonly used to enhance post-operative analgesia following orthopedic surgery as arthroscopic surgeries. Nevertheless, recent reports of severe complications due to the use of intra-articular local anesthetic have raised concerns. OBJECTIVES: The study aims to assess use of vitamin C in reducing adverse effects of the most commonly employed anesthetics - ropivacaine, bupivacaine and lidocaine - on human chondrocytes. METHODS: The chondrocyte viability following exposure to 0.5% bupivacaine or 0.75% ropivacaine or 1.0% lidocaine and/or vitamin C at doses 125, 250 and 500 µM was determined by LIVE/DEAD assay and annexin V staining. Expression levels of caspases 3 and 9 were assessed using antibodies by Western blotting. Flow cytometry was performed to analyze the generation of reactive oxygen species. RESULTS: On exposure to the local anesthetics, chondrotoxicity was found in the order ropivacaine < bupivacaine < lidocaine. Vitamin C effectively improved the reduced chondrocyte viability and decreased the raised apoptosis levels following exposure to anesthesia. At higher doses, vitamin C was found efficient in reducing the generation of reactive oxygen species and as well down-regulate the expressions of caspases 3 and 9. CONCLUSIONS: Vitamin C was observed to effectively protect chondrocytes against the toxic insult of local anesthetics ropivacaine, bupivacaine and lidocaine.